Chlorophyll-based photocatalysts and their evaluations for methyl orange photoreduction - Joshi, Meenal M.; Kamble, Sanjay R.; Labhsetwar, Nitin K.; Parwate, D. V.; Rayalu, Sadhana S. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Immobilization of chlorophyll on different functionalized mesoporous materials has been attempted. The replacement of butanediol with monoethanol amine has resulted in increase in chlorophyll loading by a factor of two. The maximum immobilization of chlorophyll was on MCM-41 functionalized with monoethanolamine MCM-41/MEA/Chl) as compared to other mesoporous materials. This material has been characterized using XRD, UV-vis diffuse reflectance spectroscopy, scanning electron microscopy (SEM-EDX) and fluorescence spectroscopy. The photocatalytic reduction of methyl orange (MO)was studied using MCM-41/MEA/Chl as photocatalyst under the visible light. The photocatalytic reduction of MO was 0.396 mg/g of MCM-41/MEA/Chl photocatalyst as compared to 0.508 mg/g of TiO(2) for that of Degussa P-25 photocatalyst. The effect of various operating parameters like catalyst loading, initial concentration and intensity of light has also been studied. Photocatalytic property of chlorophyll-based photocatalytic material indicates that chlorophyll acts as a reaction center, which absorbs visible light and generates electron, which is transferred to different electron acceptors reducing MO into derivative of hydrazine. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chlorophyll-based photocatalyst; Mesoporous material; Methyl orange; Photoreduction

Defluoridation of drinking water using chemically modified bentonite clay - Kamble, Sanjay P.; Dixit, Priyadarshini; Rayalu, Sadhana S.; Labhsetwar, Nitin K. (Desalination, 2009)
Adsorption potential of metal oxide (lanthanum, magnesium and manganese) incorporated bentonite clay was investigated for defluoridation of drinking water using batch equilibrium experiments to gain insight of adsorption behavior, kinetics and mechanisms of adsorption of fluoride ion. The effect of various physicochemical parameters such as pH, adsorbent dose, initial fluoride concentration and the presence of interfering co-ions on adsorption of fluoride has been investigated. The 10%La-bentonite shows higher fluoride uptake capacity for defluoridation of drinking water as compared to Mg-bentonite, Mn-bentonite and bare bentonite clay. The uptake of fluoride in acidic pH was higher as compared to alkaline pH. The equilibrium adsorption data fitted reasonably well in both Langmuir and Freundlich isotherm models. It was also observed that in the presence of certain co-existing ions can have positive effect on removal of fluoride, while carbonate and bicarbonate anions show deleterious effect. The rate of adsorption was reasonably rapid and maximum fluoride uptake was attained within 30 min. The modified adsorbent material shows better fluoride removal properties for actual field water, which could be due to the positive effect of other co-ions present in the field water. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 10%La-bentonite; Defluoridation; Kinetic modeling; Langmuir and Freundlich adsorption isotherms; Water treatment

Visible light induced photoreduction of methyl orange by N-doped mesoporous titania - Joshi, Meenal M.; Labhsetwar, Nitin K.; Mangrulkar, Priti A.; Tijare, Saumitra N.; Kamble, Sanjay P.; Rayalu, Sadhana S. (Applied Catalysis A-General, 2009)
N-doped mesoporous titania was synthesized using templating method. Biopolymer chitosan was used as a template and also as a nitrogen source along with ammonium hydroxide. Three different types of N-doped mesoporous titania were synthesized by varying composition of chitosan and titania precursor. These photocatalysts were characterized using XRD, BET-SA, FTIR, UV-DRS, SEM-EDX and XPS analysis. The photocatalytic activity of mesoporous titania was studied by methyl orange (MO) photoreduction reaction. From the experimental results it was observed that the N-doped mesoporous titania (1:2) gives the highest photocatalytic reduction of MO as compared to N-doped mesoporous titania prepared with (1:1) and (1:3) stoichiometry. This could be due to the optimal level of `N' incorporation in the N-doped mesoporous titania (1:2). Photocatalysts reduce the MO dye into derivative of hydrazine. Photoactivity of N-doped mesoporous titania (1:2) is 1.0721 mg of MO reduced per g of TiO2 vis-a-vis 0.508 mg of MO reduced per g of TiO2 for Degussa P25 photocatalyst. The effect of various operating parameters like photocatalyst loading. initial concentration and intensity of light also has been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: biopolymer; Chitosan; MO photoreduction; N-doped mesoporous titania; Visible active photocatalyst

Hydrogen evolution by a low cost photocatalyst: bauxite residue - Mangrulkar, Priti A.; Joshi, Meenal V.; Kamble, Sanjay P.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
Bauxite residue or red mud which is an aluminium industry waste has been used as a novel low cost photocatalyst active in visible light for the generation of hydrogen from water. The driving force behind the use of bauxite residue as a photocatalyst is not only the fact that it is widely available but also bauxite residue is a fine grained mixture of oxides and hydroxides (Fe(2)O(3), TiO(2), SiO(2), and Al(2)O(3), Al(OH)3). The photocatalyst was characterized with respect to BET-SA, UV-DRS, XRD, SEM and EDX. Hydrogen yield of 4600 mu mol/h/g of TiO(2) was achieved as compared to hydrogen evolution rate of 164 mu mol/h/g of TiO(2) for commercially available titania Degussa P-25. However, the hydrogen evolution was 20.85 mu mol/h/g of photocatalyst. The results suggest that bauxite residue appears to be a novel low cost photocatalyst. The various operating conditions of photocatalytic hydrogen generation were studied which include amount of catalyst, illumination intensity, illumination time, effect of various sacrificial donors etc. (C) 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Aluminium industry waste; Bauxite residue; Hydrogen generation; Red mud; Sacrificial donors

Influence of zeolitic structure on photoreduction property and hydrogen evolution reaction - Chatti, Ravikrishna V.; Dubey, Nidhi; Joshi, Meenal V.; Labhsetwar, Nitin K.; Joshi, P. N.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
A new photocatalytic material developed by supporting TiO(2) in combination with transition metal ion like cobalt and heteropolyacid (HPA) on the surface is facilitating enhanced photoreduction of water and methyl orange Zeolites being a solid acid play an important role in the electron transfer reaction, facilitated by the Lewis acid sites in the form of aluminium ions In the present work, four different zeolite matrices namely, NaY zeolite, ultrastable zeolite Y, beta zeolite and titanium silicate-1 have been used for the synthesis of new photocatalytic materials These materials have been evaluated for water splitting by an initial screening procedure using methyl orange photoreduction The photocatalyst containing Na Y has emerged as a potential photocatalyst with hydrogen evolution rate of 2730 mu mol/h/g of TiO(2) Hydrogen evolution was not observed for the composite photocatalysts synthesized using the other zeolite matrices It has been observed that physicochemical properties like Si/Al ratio, acidity and basicity of the zeolite support have a tremendous influence on the photoreduction property of these zeolite matrices (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: H(2) evolution; Lewis acidity; Si/Al ratio; water splitting; Zeolite structure

Photocatalytic degradation of phenolics by N-doped mesoporous titania under solar radiation - Mangrulkar, Priti A.; Kamble, Sanjay P.; Joshi, Meenal M.; Meshram, Jyotsna S.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Photoenergy, 2012)
In this study, nitrogen-doped mesoporous titania was synthesized by templating method using chitosan. This biopolymer chitosan plays the dual role of acting as a template (which imparts mesoporosity) and precursor for nitrogen. BET-SA, XRD, UV-DRS, SEM, and FTIR were used to characterize the photocatalyst. The doping of nitrogen into TiO2 lattice and its state was substantiated and measured by XPS. The photocatalytic activity of the prepared N-doped mesoporous titania for phenol and o-chlorophenol degradation was investigated under solar and artificial radiation. The rate of photocatalytic degradation was observed to be higher for o-chlorophenol than that of phenol. The photodegradation of o-chlorophenol was 98.62% and 72.2%, while in case of phenol, degradation to the tune of 69.25% and 30.58% was achieved in solar and artificial radiation. The effect of various operating parameters, namely, catalyst loading, pH, initial concentration and the effect of coexisting ions on the rate of photocatalytic degradation were studied in detail.

Influence of carbon based supports on selectivity behavior of diols and propanol in Ru catalyzed glycerol hydrogenolysis - Mane, Rasika B.; Patil, S.; Shirai, Masayuki; Rayalu, Sadhana S.; Rode, Chandrashekhar V. (Applied Catalysis B: Environmental, 2017)
Activated carbon (AC) and three graphite materials were studied as supports for Ru catalyzed glycerol hydrogenolysis to propanediols and 1-propanol. Structural characteristics of AC and graphite materials were found to greatly affect the reducibility and particle size of supported Ru and hence, the activity and product distribution in glycerol hydrogenolysis. XRD of graphite materials showed distinctly (002) plane having highly organized layered structure and the peak intensity decreased in the order of Ru/KS150 > Ru/HSAG100 > Ru/KS6 due to decrease in the graphite sheet thickness. In Raman, the intense D band in HSAG100 compared to that in KS6 and KS150 samples indicated its highly amorphous nature or mixed carbon hybridization. Glycerol conversion for Ru on AC was higher than that on graphite and among different graphites, it showed a descending activity order of Ru/KS6 > Ru/HSAG100 > Ru/KS150. The product distribution for AC and HSAG100 supported Ru was similar, giving 1-propanol (45%) alongwith 1,2-propanediol (1,2-PDO) (37%) and 1,3-propanediol (1,3-PDO) (9–11%). For graphite supports, availability of Ru although bigger in size (4–5 nm), would be higher on the surface than in case of AC which formed deep hydrogenolysis products like 1-, 2- propanol, ethanol etc.
Keywords: activated carbon; Amorphous carbon; catalysis; Glycerol; Glycerol conversions; Glycerol hydrogenolysis; graphite composites; Graphite supports; Hydrogenolysis; Hydrolysis; layered structures; Particle size; Product distributions; Propanediols; Propanol; Selectivity behavior; Structural characteristics; Structural effect; Structural effects